Psychological Safety of Volunteers During the War - Pidbutska, Nina; Knysh, Anastasiia; Demidova, Yuliia (Journal of Education Culture and Society, 2023)
Aim. The article is aimed at determining the indicators of psychological safety inherent in volunteers with signs of emotional exhaustion in combat zones. Methods. The study included the following methods: a) testing: Emotional Exhaustion Questionnaire (EEQ), Psychological Safety of Individual Questionnaire; b)statistical analysis: methods of descriptive statistics (percentage, minimum, maximum, range, standard error, mean, standard deviation). The group of respondents included 48 people, who were involved in volunteer activities in the Kharkiv region of Ukraine from March 2022 up to November 2022. Results. It was determined that the largest subgroup in the general group of respondents were volunteers with a high level of emotional exhaustion (46%) – these are people who feel general tension and do not remember the last time they experienced positive emotions. Among all the indicators of psychological safety, the indicators of moral-communicative and internal comfort turned out to be the least developed. Conclusions. Volunteer groups need specially organized psychological help and support, just like military or military medics. The constant danger of the activity, the need to be in contact with different people, moral fatigue lead to rapid emotional exhaustion and can causehealth disorders or even cost the volunteer’s life.